Congenital Adrenal Hyperplasia (CAH) - Causes, Diagnosis, Symptoms, Treatment - Oskar Targoński; Marta Targońska; Adrianna Madej; Adrian Suława; Julia Furgalska; Sebastian Fedorowicz; Aneta Basiak; Aleksander Ptasiński; Rafał Niekurzak; Agnieszka Buczek (Quality in Sport)
Introduction and Purpose: Congenital adrenal hyperplasia represents a group of genetic disorders characterized by improper adrenal steroidogenesis, resulting in deficiency or absence of cortisol and/or aldosterone, and varying degrees of disturbances in sexual development. The aim of this study is to raise awareness about the disease, enabling early diagnosis and contributing to reducing neonatal mortality, as the first clinical manifestation of CAH can be the life-threatening salt-wasting syndrome.